Safety and effectiveness of thermal radiofrequency applied to the musculocutaneous nerve for patients with spasticity - Otero-Villaverde, Sergio; Formigo-Couceiro, Jacobo; Martin-Mourelle, Rosa; Montoto-Marques, Antonio (Frontiers in Neurology, 2024)
Objective Evaluate safety and effectiveness of thermal radiofrequency in the musculocutaneous nerve in patients with focal elbow flexor spasticity. Design Ambispective observational follow-up study. Patients with focal spasticity secondary to central nervous system injury with elbow flexor pattern who received thermal radiofrequency treatment in the musculocutaneous nerve between 2021 and 2023 were included. Subjects 12 patients. Methods Ultrasound-guided thermal radiofrequency was applied to the musculocutaneous nerve at 80°C for 90 s. Effectiveness was assessed prior to thermal radiofrequency and at 6 months using scales to measure pain (VAS), spasticity (MAS), disability (DAS), quality of life (SQol-6D), patient-perceived and physician-perceived satisfaction (PIG-C, PGA), and goal attainment (GAS). Elbow joint range of motion was evaluated via goniometry. Safety was evaluated by assessing side effects. Results Patients had statistically significant improvements in spasticity (p = 0.003), severe elbow flexion (p = 0.02), pain (p = 0.046), functioning (p < 0.05), and spasticity-related quality of life (p < 0.05 in three sections). Furthermore, treatment goals were attained. Patient- and physician-perceived clinical improvement was achieved. Regarding side effects, two patients had dysesthesia that was self-limiting, with maximum duration of 1 month. Conclusion Thermal radiofrequency in the musculocutaneous nerve can be a safe, effective treatment for patients with severe spasticity with an elbow flexor pattern.